Does pay transparency affect the gender wage gap? Evidence from Austria - Andreas Gulyas; Sebastian Seitz; Sourav Sinha (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study the 2011 Austrian Pay Transparency Law, which requires firms above a size threshold to publish internal reports on the gender pay gap. Using an event-study design, we show that the policy had no discernible effects on male and female wages, thus leaving the gender wage gap unchanged. The effects are precisely estimated and we rule out that the policy narrowed the gender wage gap by more than 0.4 p.p.. Moreover, we do not find evidence for wage compression within establishments. We discuss several possible reasons why the reform did not reduce the gender wage gap.
Keywords: J08; J31; J38; J78; 330; Gender Pay Gap; Pay Transparency